Manajemen Perpustakaan Digital Dalam Mendukung Budaya Literasi Di Smpn 3 Palopo - Herlina; , Firman Patawari; Sarmila (Hikamatzu | Journal of Multidisciplinary, 2025)
This study explores the role of digital library management in supporting the development of a literacy culture at SMPN 3 Palopo. The research highlights how the integration of digital library systems provides easier access to learning resources, encourages students’ reading habits, and enhances teachers’ ability to deliver effective learning materials. Through qualitative analysis, it was found that the digital library not only expands the variety of accessible references but also fosters students’ critical thinking, creativity, and independence in learning. Furthermore, the implementation of digital library management contributes to creating an academic environment that aligns with the demands of the digital era, thereby strengthening the literacy culture within the school community.